Inhibitory effect of biofilm-forming Lactobacillus plantarum PA21 isolated from tropical plant pandanus on foodborne pathogens - Jalilsood, Tannaz (2017)
Bacterial biofilms are a preferred mode of growth for many types of microorganisms in their natural environments. The ability of pathogens to integrate within a biofilm is pivotal to their survival. Alternatively, new opportunities are now arising with the rapidly expanding potential of lactic acid bacteria (LAB) biofilms as biocontrol agents against foodborne pathogens. The present study was carried out to evaluate the effectiveness of a new Lactobacillus plantarum PA21 against several pathogenic and food-spoilage bacteria in the biofilm and planktonic phases. In addition, the attention was focused on the use of this isolate as a new host to investigate Lactobacillus key regulatory proteins in biofilm formation for further biotechnological applications. Towards this objective, LAB was isolated from tropical plant Pandanus amaryllifolius. A new isolate was identified as Lactobacillus plantarum PA21 which showed biofilm formation in either pure culture and or in combination with several pathogenic and food-spoilage bacteria, such as Salmonella enterica, Bacillus cereus, Pseudomonas fluorescens, and Aeromonas hydrophila. Exposure to Lb. plantarum PA21 has significantly reduced the number of P. fluorescens, A. hydrophila and B. cereus cells in the planktonic and biofilm forms over 2-, 4- and 6-day time periods. However, despite the reduction in S. enterica cells, this pathogen showed the most resistance when co-cultured with Lb. plantarum PA21 and could not be eliminated entirely, either in the planktonic or biofilm phase. Lb. plantarum PA21 was also found to be able to constitutively express gfp (green fluorescent protein) gene when transformed with the expression vector pMG36e, suggesting its capability of being a host for heterologous protein production. Moreover, the gene expression ability of PA21 has allowed the identification the EAL containing protein for the first time in Lactobacillus spp, which inversely regulates biofilm formation and acts as a key regulatory protein in biofilm dispersal. By reading the optical density and viable cell count results, EAL21 overexpression in PA21 showed decreased adhesion compared to the wild type strain and significantly lowered the mean of cell counting results by 4.7 log.